Entrepreneurship development in China - He, Xiaohong (Henry Stewart Talks, 2013)
China private enterprises, Entrepreneurial empowerment for a better life, Major entrepreneurial clusters in Zhejiang, Cluster networks, The world socks capital, Income and standard of living, Population living under poverty: Zhejiang vs. China, Capitalistic approach with socialistic mindset, Village led by entrepreneurial CCP secretary, An entrepreneurial dream for everyone, China 12th five-year plan, Environment paid high price, Issues facing the development